The siren song of aesthetics? Domain differences and creativity in engineering and design. (January 2019) - Cropley, David H; Kaufman, James C
For many years, researchers have debated the role of "domain" in creativity. Opinion remains divided, but a common view is that creativity is a combination of domain-general elements, coupled with domain-specific manifestations, usually in the form of different kinds of products. Discussions of domains and creativity frequently take place in very broad, thematic terms, differentiating only between Arts and Sciences, with less attention given to differences within domains. The goal of this paper is to explore a single technological domain, studying differences between the micro-domains of Engineering and Industrial Design. Do engineers and industrial designers differ when evaluating the creativity of products? If they differ, what might be the underlying drivers of these differences? Contrary to expectations, not only were there significant differences between these groups, but evidence presented in this study suggests that engineers have difficulty differentiating between aesthetics and functionality, as components of product creativity, in contrast to industrial designers, who seem to possess a more discriminating eye.